308 Fine Needle Aspiration Cytology vs Ultrasound Guided Core Biopsy in the Diagnosis of Parotid Neoplasia: An Up-to-Date Review. (19th August 2022) - Karunaratne, N; Hurry, K; Westley, S; Ramesar, K; Williams, M; Howlett, D
Abstract: Aim: Parotid tumours account for 80% of salivary neoplasms. Regarding diagnostic techniques, fine needle aspiration cytology (FNAC) has long been the technique for tissue sampling and can be optimised with ultrasound or presence of a cytopathologist. USCB differs in that it obtains a core of tissue which allows preservation of the tissue architecture. The authors performed a literature review to provide an update on current practice and outcomes of both techniques Method: A literature review of EMBASE, Medline, PubMed and Google Scholar were conducted. Regarding USCB, four systematic reviews and meta-analyses were identified, alongside three other studies that were not included within these papers. Regarding FNAC, three systematic reviews and meta-analyses were identified, alongside seven other studies, not included within these papers, using optimised FNAC in sample sizes of over fifty. Results: USCB has higher sensitivity, specificity, and lower non-diagnostic rates than optimised fine needle aspiration cytology (FNAC). It also has a significantly higher sensitivity for the detection of malignancy. Complications post-USCB are uncommon, with only one reported case of tumour seeding and no cases of permanent facial nerve dysfunction. The technique is less operator dependent than FNAC, with less variation in results between institutions. Conclusions: USCB can be considered as the optimum tool of choice for diagnosis of parotid neoplasia. This would particularly be the case in centres utilising FNAC with high non-diagnostic rates or reduced diagnostic accuracy when compared to USCB published data or in centres establishing a new service.